Extra-Tidal Members and Dynamics of the Open Cluster NGC 6705 - Chen Zhou; Xinhua Gao (Applied Sciences)
In this study, we utilized Gaia-DR3 astrometric data combined with the density-based spatial clustering of applications with noise (DBSCAN) algorithm to thoroughly investigate the dynamics and extra-tidal members of the open cluster NGC 6705. We determined more than 1900 cluster members within ∽12 pc of the cluster. We estimated the core and tidal radii to be 3.11 ± 0.21 arcmin (∽2 pc) and 20.02 ± 0.71 arcmin (∽13 pc), respectively, based on the cluster members. A Gaussian mixture model (GMM) was used to segregate the core and halo components of the cluster. The major and minor axes of the core and halo were determined through principal component analysis (PCA). The semi-major axis lengths of the core and halo were estimated to be <semantics>7′</semantics> (∽4.5 pc) and <semantics>21′</semantics> (∽13.6 pc), respectively. Additionally, the axis ratios of the core and halo were found to be e∽0.89 and e∽0.80, respectively, suggesting that the halo was significantly affected by the external tidal field. We detected a clear mass segregation effect within the cluster. Furthermore, we also detected some extra-tidal members around the cluster, implying that these stars are being lost from the cluster because of gravitational interactions with the Milky Way. This work provided a comprehensive characterization of NGC 6705, revealing its tighter structure, ongoing mass segregation, and potential star loss.